Development of Interactive Augmented Reality Cards as a Learning Media for the Solar System in Space Adventure Games for Grade VI Elementary Schools - Awalia Anzilni; Hafizah Ghany Hayudinna (Universitas Negeri Malang, 2025)
Abstract: Elementary school children are at the concrete operational stage so they need learning media such as Augmented Reality (AR) to understand abstract material. At SD Negeri 01 Gumawang, despite having the potential to use technology, teachers still have limitations in innovation and implementing effective learning media. This study aims to develop an interactive AR through the